2005
DOI: 10.1017/s1049023x00002454
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Traumatic Deaths in Nigeria

Abstract: Introduction:The number of deaths due to trauma from road traffic accidents (RTAs), and from the use of firearms either for homicide or armed robbery, ethnic conflicts, and other events, such as flooding, explosions from petroleum products, and religious violence, is on the rise in Nigeria. This preliminary study is a comparative analysis of the frequency of deaths caused by RTAs and the deaths caused by the use of firearms during armed robbery. The study sought to identify the number of traumatic deaths cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
1
9
0
4
Order By: Relevance
“…Studies from different parts of Nigeria have shown that RTA is the most common cause of traumatic death [6][7] accidental death [8] as well as death due to surgical emergencies [9]. In all these and similar reports, abdominal injury with splenic damage was very common both in children as well as in adults [10,11].…”
Section: Discussionmentioning
confidence: 96%
“…Studies from different parts of Nigeria have shown that RTA is the most common cause of traumatic death [6][7] accidental death [8] as well as death due to surgical emergencies [9]. In all these and similar reports, abdominal injury with splenic damage was very common both in children as well as in adults [10,11].…”
Section: Discussionmentioning
confidence: 96%
“…High level of unemployment has led to increasing number of illtrained commercial motorcycle riders; ethno-political violence and armed robbery are on the rise in the country. 3,7 Due to persistent energy crisis, there is frequent adulteration of petroleum products, storage of petrol around residential buildings for fuelling domestic power generators, sporadic fire accidents and burns. These problems have contributed to high trauma related morbidity and mortality in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma is one of the leading causes of morbidity and mortality worldwide but constitutes an exceptionally huge burden in countries with limited resources 1,2 . In Nigeria, the number of deaths due to trauma-induced injuries is on the increase 3,4 . Major trauma refers to severe injuries often presenting as life threatening emergency, requiring either immediate surgical intervention or intensive care or both 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria has one of the highest rates of fatal road traffic accidents worldwide and the number is still rising (Ehikhamenor and Ojo, 2005). Most accidental deaths were associated with head injury or multiple severe injuries.…”
Section: Discussionmentioning
confidence: 99%